Synthesis of some new heterocyclic compounds derived from 2-Chloro-3-formyl quinoline - Ala Ayoob; Fatma Mohmood (College of Education for Pure Sciences, 2013)
ABSTRACT In this paper the Synthesis of some substituted 2-Chloro-3-formyl quinoline (2a-d) by treating various substituted acetanilide or 1-(4-substituted phenyl) ethanone oxime with POCl3 in dimethyl formamide. It proceeds through Vilsmeier - Haack cyclization. The condensation of 2-chloro-3-formylquinoline with p-Hydroxyacetophenone, 2-acetyl pyridine, 2-acetyl furan or 3-acetyl indole via Claisene- Schmiatcondensations gives quinolinylchalcone (4a - d). Newpyrazoline derivatives were synthesized by condensing the appropriate chalcone (4a) with hydrazine hydrate or phenylhydrazine (10 - 11). Oxazole (12) is reported from compound (4a) and hydroxyl amine hydrochloride is in basic medium. The reaction of chalcone (4a) with urea, thiourea or quinidine hydrochloride gives pyrimidine-2-one (7), pyrimidine-2-thiol (8) or 2- amino pyrimidine (9) respectively.Oxirane (6) prepared from reaction of chalcone (4a) with hydrogen peroxide in basic medium. The reaction of chalcone (4a) with bromine gives dibromide (5). The structures of synthesized compounds were confirmed by spectral and physical methods.